Unravelling Stilpnopappus (Lepidaploinae, Vernonieae, Asteraceae) diversity: A new species from Bahia, Brazil - Remor, Danielle; Borges, Kairo Michel Lima; Siniscalchi, Carolina M.; Loeuille, Benoît (Phytotaxa, 2026)
A new species of Stilpnopappus (Vernonieae, Asteraceae) from the Caatinga, occurring mainly in northern Bahia, Brazil, in the São Francisco River Basin, is hereby described. Stilpnopappus roqueae is commonly misidentified amongst herbarium specimens as S. trichospiroides, but the new species differs mostly in the involucre shape (hemispherical vs. campanulate), intermediate phyllary shape (elliptic to oblong, obovate, pandurate vs. lanceolate), apex (obtuse to rounded, apiculate vs. acute to acuminate) and margins (entire, rarely revolute apically vs. ciliate at apex or along its entire length), inner phyllary margins (entire vs. short apically ciliate) and apex (acute, usually apiculate vs. long acuminate). A morphological description, distribution map, a text figure and composite plates illustrating the new species and taxonomic notes are provided.